2018
DOI: 10.1002/smll.201802086
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design Principles for the Transport and Subcellular Distribution of Nanomaterials into Plant Protoplasts

Abstract: The ability to control the subcellular localization of nanoparticles within living plants offers unique advantages for targeted biomolecule delivery and enables important applications in plant bioengineering. However, the mechanism of nanoparticle transport past plant biological membranes is poorly understood. Here, a mechanistic study of nanoparticle cellular uptake into plant protoplasts is presented. An experimentally validated mathematical model of lipid exchange envelope penetration mechanism for protopla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
152
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 115 publications
(161 citation statements)
references
References 92 publications
(158 reference statements)
7
152
2
Order By: Relevance
“…QD with β-cyclodextrin molecular baskets conjugated with targeting peptides (Chl-QD) allow the targeted delivery of biochemical cargoes into chloroplasts. The β-CD molecular basket composed of seven cyclic oligosaccharides enables "hostguest" formation with ascorbic acid or methyl viologen 36,37 and can form inclusion complexes with a broad range of biomolecules 12,17,38,39 . Furthermore, QD have a high and stable fluorescence enabling in vivo tracking within plant tissues and cellular compartments 40 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…QD with β-cyclodextrin molecular baskets conjugated with targeting peptides (Chl-QD) allow the targeted delivery of biochemical cargoes into chloroplasts. The β-CD molecular basket composed of seven cyclic oligosaccharides enables "hostguest" formation with ascorbic acid or methyl viologen 36,37 and can form inclusion complexes with a broad range of biomolecules 12,17,38,39 . Furthermore, QD have a high and stable fluorescence enabling in vivo tracking within plant tissues and cellular compartments 40 .…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the zeta potential of Chl-QD is significantly lower than MPA-QD (P < 0.001) ( Fig. 2c) indicating that models based on increased nanoparticle charge for promoting chloroplast delivery 12,38,39 are not sufficient to predict plant organelle localization of nanomaterials guided by biomolecule recognition motifs in plants in vivo.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[32,33] In addition, their surface properties can be engineered to target different plant organs or subcellular organelles. [34][35][36] Arsenite is chosen as the target analyte because it is the predominant form of arsenic in anaerobic paddy soils which can be taken up efficiently by crops through silicon transporters in the roots. [12,37,38] Previous studies have shown that guanine (G) and thymine (T) nucleotides can form strong hydrogen bonds with the hydroxy (OH) groups of arsenite.…”
Section: Doi: 101002/adma202005683mentioning
confidence: 99%
“…Nanoparticles with dimensions below the size exclusion limit of the cell wall (~20-50 nm) have the ability to access the plant cell interior 111 . It has been shown that the zeta potential and size of nanoparticles govern their subcellular localization within plant cells, enabling the specific targeting of various compartments such as the chloroplasts and the cytosol 75,112,113 . Furthermore, targeting moieties can be grafted onto the surface of nanostructures to direct their localization to the nucleus, mitochondria or other organelles within a plant cell 114,115 .…”
Section: New Opportunities Afforded By Species-independent Toolsmentioning
confidence: 99%